2021
DOI: 10.1097/pec.0000000000002600
|View full text |Cite
|
Sign up to set email alerts
|

The Toddler's Fracture

Abstract: Objective:The tibial toddler's fracture is an important diagnosis in both emergency and urgent care, presenting as acute onset lower extremity pain or limping in a young child. Diagnosis and management may be challenging because of an extensive differential diagnosis. The objectives of this study were to provide an overview of the toddler's fracture and to guide clinicians by summarizing up to date literature for both diagnosis and management this common condition.Methods: This study analyzed literature from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…37 Some studies have even suggested no immobilization, given the stability of these injuires. 38 While it would be reasonable to immobilize these in a long-leg splint or cast, neither leads to improved outcomes and is associated with increased orthopedic visits and health care costs. 39 Nondisplaced fractures of the midshaft of the tibia are amenable to a posterior long-leg splint with non-weight-bearing instructions and referred for urgent orthopedic outpatient follow-up.…”
Section: Tibiamentioning
confidence: 99%
See 1 more Smart Citation
“…37 Some studies have even suggested no immobilization, given the stability of these injuires. 38 While it would be reasonable to immobilize these in a long-leg splint or cast, neither leads to improved outcomes and is associated with increased orthopedic visits and health care costs. 39 Nondisplaced fractures of the midshaft of the tibia are amenable to a posterior long-leg splint with non-weight-bearing instructions and referred for urgent orthopedic outpatient follow-up.…”
Section: Tibiamentioning
confidence: 99%
“…These injuries are safe for immobilization in a CAM (controlled ankle movement) walking boot and outpatient orthopedic follow-up 37 . Some studies have even suggested no immobilization, given the stability of these injuires 38 . While it would be reasonable to immobilize these in a long-leg splint or cast, neither leads to improved outcomes and is associated with increased orthopedic visits and health care costs 39 .…”
Section: Lower Extremitymentioning
confidence: 99%
“…1 Due to its inherent stability, there is little risk of displacement during the healing process. 2 In cases of a negative radiograph, any toddler with a limp and suspicion for a lower-leg fracture is treated similarly as a presumed toddler's fracture. 3 Various treatment options are available, 4 including immobilization with a cast or splint, with a walking boot or brace, or without immobilization.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Due to its inherent stability, there is little risk of displacement during the healing process. 2 In cases of a negative radiograph, any toddler with a limp and suspicion for a lower-leg fracture is treated similarly as a presumed toddler’s fracture. 3 …”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] Children’s psychological and behavioral development is more mature than that in early childhood, but their experience in life, self-protection ability, concentration and self-control are still not strong. [ 3 ] When children enter school life at this stage, their parents’ awareness of protection is more relaxed than before, and school-age children’s self-safety awareness is not strong, making the school-age children prone to upper or lower limb fractures. [ 4 , 5 ] In addition to correct treatment after fracture, the functional exercise of the affected limb after treatment is very important.…”
Section: Introductionmentioning
confidence: 99%